2016
DOI: 10.1103/physrevb.94.085413
|View full text |Cite
|
Sign up to set email alerts
|

Spin- and valley-polarized transport in a monolayer ofMoS2

Abstract: We investigate dc and ac transport in a monolayer of MoS 2 in the presence of an effective mass asymmetry, a momentum-dependent term, and an out-of plane or in-plane Zeeman term. Analytical results are presented for both dc and ac conductivities in the framework of linear response theory. We show that the spin-Hall conductivity exhibits a strong dependence on the strength of the spin-orbit interaction while both spin-and valley-Hall conductivities show a very weak dependence on the temperature. The sum of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…It should be noted that we use a constant relaxation time for the following calculations where the specific scattering events are not considered. Very recently, the intraband optical conductivity for ML-MoS 2 has also been calculated [50], and the evaluation of the relaxation time by impurity scattering had been discussed in Ref. [51].…”
Section: Optical Conductivitymentioning
confidence: 99%
“…It should be noted that we use a constant relaxation time for the following calculations where the specific scattering events are not considered. Very recently, the intraband optical conductivity for ML-MoS 2 has also been calculated [50], and the evaluation of the relaxation time by impurity scattering had been discussed in Ref. [51].…”
Section: Optical Conductivitymentioning
confidence: 99%
“…He et al [28] investigated the magnetic properties of nonmetal atoms absorbed monolayer MoS 2 by first-principles calculations. The spin-and valley-dependent magneto-optical properties [29], the quantum magnetotransport [8,12,30], the spin-and valley-polarized transport [31], and the effect of doping and strain modulations on electron transport [32], as well as the thermal conductivity and phonon linewidths [33] have been investigated in this interesting system.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the spin-polarized current is easily controlled by the spin and valley Zeeman terms in this material. The spin-orbit interactions and spin and valley filtering have been also demonstrated to significantly affect the transport gap [14] and spin-and valley-Hall conductivities [15] in monolayer MoS 2 . Yuan et al [17] studied the dependence of electron transport on the spin and valley polarization in monolayer MoS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Spintronics and valleytronics have been playing increasingly important roles and considered as the keys of the new period of the electronics technology [9]. The spin-and valleypolarized transport have been proved to be the most vital properties of the 2D materials and have been of significant interest and studied widely [14][15][16][17][18]. When studying the electron transport through the barriers in monolayer WSe 2 , Tahir et al [16] found that the spin splitting is essential to the valley-polarized transport.…”
Section: Introductionmentioning
confidence: 99%